2018
DOI: 10.1161/circulationaha.117.033067
|View full text |Cite
|
Sign up to set email alerts
|

Time to Epinephrine Administration and Survival From Nonshockable Out-of-Hospital Cardiac Arrest Among Children and Adults

Abstract: Among OHCAs with nonshockable initial rhythms, the majority of patients were administered epinephrine >10 minutes after EMS arrival. Each minute delay in epinephrine administration was associated with decreased survival and unfavorable neurological outcomes. EMS agencies should consider strategies to reduce epinephrine administration times in patients with initial nonshockable rhythms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
116
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 29 publications
3
116
3
5
Order By: Relevance
“…During in-hospital cardiac arrest, Donnino et al noted a stepwise reduction in survival and favourable neurological outcome with delays in adrenaline administration exceeding 1-3 min [10]. In OHCA, Hansen et al found that every minute delay to the administration of adrenaline decreased survival (OR 0.96, 95% CI 0.95-0.98) and favourable neurological outcomes (OR 0.94, 95% CI 0.89-0.98) [33]. By contrast, the present study was consistent with Ewy et al in finding no difference in longer term outcomes according to the time of adrenaline administration for patients with nonshockable rhythms [29].…”
Section: Discussionmentioning
confidence: 99%
“…During in-hospital cardiac arrest, Donnino et al noted a stepwise reduction in survival and favourable neurological outcome with delays in adrenaline administration exceeding 1-3 min [10]. In OHCA, Hansen et al found that every minute delay to the administration of adrenaline decreased survival (OR 0.96, 95% CI 0.95-0.98) and favourable neurological outcomes (OR 0.94, 95% CI 0.89-0.98) [33]. By contrast, the present study was consistent with Ewy et al in finding no difference in longer term outcomes according to the time of adrenaline administration for patients with nonshockable rhythms [29].…”
Section: Discussionmentioning
confidence: 99%
“…This 1‐minute difference in epinephrine concentration may be a critical factor in the potential treatment of a patient with anaphylaxis because mismanagement of anaphylaxis with delayed recognition of allergic symptoms or delayed treatment with epinephrine can be fatal 3,39‐42 . Indeed, there is a negative correlation between the time to epinephrine treatment and a patient's rate of survival 17 . Thus, immediate treatment and epinephrine absorption is crucial in the treatment of anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, cost effectiveness and autoinjector availability are potential barriers for certain patients with severe allergy 12,16 . These patient concerns may lead to lack of or delayed epinephrine treatment, which decreases the rate of survival in the event of anaphylaxis 17 …”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have reported that these procedures were less effective in providing good neurological prognoses, 11,12 two recent studies have shown that early performance of these procedures was useful in non-shockable rhythm patients. 17,18 In physicianstaffed ambulances, the use of adrenaline and endotracheal intubation might be initiated earlier than in EMS ambulances.…”
Section: Discussionmentioning
confidence: 99%